Letter (copy) - Tewson, Vincent
025a-0017-001 International. HVT/AC/DT/257. Gen 35/17/47. 10th December, 1940. Mr. J.B. Luzmore, Immigration Branch, Home Office, P.O. Box No. 2. BOURNEMOUTH. Dear Mr. Luzmore, I have your letter of the 7th of December in which you ask as to supply you with an up-to-date list of the Spanish seamen for whom Congress is continuing to be responsible, and to give you information about the whereabouts so far as they are known, of eight other Spaniards. I am putting the necessary work in hand and hope to be able to write to you again towards the end of the week. I hope you are finding your new quarters congenial. Yours sincerely, Assistant Secretary. 292/946/25a/17